2002
DOI: 10.1046/j.1365-2516.2002.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of recombinant factor VIIa administered by continuous infusion to haemophilia patients with inhibitors

Abstract: We have prospectively monitored treatment of haemophilia patients with inhibitors by recombinant factor VIIa (rFVIIa) administered by continuous infusion to obtain more insight in the underlying factors of the clinical efficacy of this administration method. At present, 43 treatment episodes of 14 different Dutch haemophilia inhibitor patients are included in the database. Analysis of the data showed a discrepancy between the efficacy of rFVIIa continuous infusion treatment of acute and surgical bleeds in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…The high thrombin concentration required for TAFI activation might also explain why continuous infusion of rFVIIa was inferior to bolus injections in bleedings in the oral cavity (in which a high fibrinolytic activity is present) since continuous infusion produces lower peak levels compared to a bolus regimen. 15 rFVIIa also enhanced TAFI activation in plasma from healthy volunteers who received the anticoagulant drug fondaparinux. 61 However, in plasma from patients with liver disease or undergoing liver transplantation, no antifibrinolytic effect of rFVIIa could be observed, most likely because TAFI activation is already optimal in these patients.…”
Section: Tafimentioning
confidence: 92%
See 1 more Smart Citation
“…The high thrombin concentration required for TAFI activation might also explain why continuous infusion of rFVIIa was inferior to bolus injections in bleedings in the oral cavity (in which a high fibrinolytic activity is present) since continuous infusion produces lower peak levels compared to a bolus regimen. 15 rFVIIa also enhanced TAFI activation in plasma from healthy volunteers who received the anticoagulant drug fondaparinux. 61 However, in plasma from patients with liver disease or undergoing liver transplantation, no antifibrinolytic effect of rFVIIa could be observed, most likely because TAFI activation is already optimal in these patients.…”
Section: Tafimentioning
confidence: 92%
“…This method, however, seems to be less effective-at least in some cases. 14,15 Adjunctive therapy with antifibrinolytic agents such as tranexamic acid is used in some instances, but its contribution remains unclear. The recovery and clearance rate of rFVIIa may vary substantially from one patient to the next.…”
Section: The Development Of Recombinant Factor Viiamentioning
confidence: 99%
“…CI was also evaluated in various bleeding settings, with the administration of rFVIIa via this method shown to be unsuccessful in patients undergoing dental surgery. 36 In an Italian multicenter study reporting on the use of CI in 25 patients, 37 hemostasis was satisfactory in 30 of 35 procedures. In an attempt to determine a likely explanation for the hemostatic insufficiency observed in the other five procedures, the authors tested the circulating factor VII:C levels.…”
Section: Dosing Issuesmentioning
confidence: 97%
“…Favorable outcomes have been published as case reports from several centers, even with a very low rate of rFVIIa infusion. [28][29][30][31][32][33][34][35][36] However, in one study, hemostatic efficacy was regarded as insufficient in patients receiving 16.5 µg/kg/hr since four out of six major operations were complicated by excessive bleeding. 35 This rate of infusion roughly compares with the consumption of rFVIIa by bolus injections at a rate of 100 µg/kg every six hours.…”
Section: Dosing Issuesmentioning
confidence: 99%
“…There are conflicting results regarding the effectiveness of a continuous infusion as it may not be efficacious to inhibit fibrinolysis. 17 Several studies have shown that surgery in hemophilia patients with high titre of inhibitors can be performed safely using rFVIIa.…”
Section: Patientmentioning
confidence: 99%